SPATIOTEMPORAL VARIATIONS AND CONTRIBUTING FACTORS OF AIR POLLUTANTS IN ALMATY, KAZAKHSTAN - Kerimray, Aiymgul; Azbanbayev, Eldar; Kenessov, Bulat; Plotitsyn, Pavel; Alimbayeva, Danara (Taiwan Association for Aerosol Research, 2020)
In this study, spatial and temporal patterns of PM10, PM2.5, NO2, SO2, and CO in Almaty, the largest city of Kazakhstan, in the period between 2013 and 2018 are explored. Severe degradation of air quality was observed from the data that were used in this study. Annual averages of PM2.5, PM10, and NO2 concentrations exceeded the WHO annual limits by 5.3, 3.9, and 3.2 times, respectively. The maximum levels were observed in the winter, while the minimum levels in the summer. Winter-to-summer difference was more noticeable for PM2.5 than for other pollutants. The winter pollution peaks demonstrate the high contribution of large- and small-scale coal combustion for heating, which could be exacerbated with lower winds and possible more frequent thermal inversions. There was a negative correlation between elevation and levels of SO2, PM2.5, and PM10, while no correlation was observed for NO2 and CO, indicating that the former group could be mainly contributed by point sources located predominantly at lower elevations (e.g., power plants) and the latter group mainly originated from nonpoint sources distributed evenly across the city (e.g., transport). Urgent measures are needed to reduce emissions from the coal-fired power plant and from the domestic heating stoves.
Keywords: Aerosol; Air quality; Atmospheric air pollution; Particulate matter; Kazakhstan; Almaty; Type of access: Open Access